Association of insulin resistance with pre-eclampsia: a case-control study - Nahar, M. Irin; Jahan, Nur Wa Bushra; Rahman, M. Sazedur; Eva, Nusrat Jahan; Khan, Farzana Farhin; Ahmed, Naorin; Parvin, Rahana; Nesa, M. Karimatun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Preeclampsia, characterized by new-onset hypertension and proteinuria after 20 weeks of gestation, is a leading cause of maternal and perinatal death. Its etiology involves vascular endothelial dysfunction, oxidative stress, and metabolic dysregulation. Evidence suggests that insulin resistance may contribute to its development by promoting vasoconstriction and endothelial injuries. This study aimed to evaluate the association between insulin resistance and preeclampsia and its correlation with blood pressure in pregnant women. Methods: A hospital-based case-control study was conducted at Department of Obstetrics and Gynaecology, Sir Salimullah Medical College Mitford Hospital, Dhaka, Bangladesh, from February 2022 to January 2023, including 50 preeclamptic and 50 normotensive pregnant women (gestational age, 20-40 weeks). Fasting plasma glucose and serum insulin were measured, and insulin resistance was calculated using the HOMA-IR index. Data were analyzed using SPSS version 24, and statistical significance was set at p<0.05. Results: Preeclamptic women had significantly higher fasting glucose (4.48±0.51 mmol/l), serum insulin (29.0±5.97 µU/ml), and HOMA-IR (3.52±0.74) compared to controls (4.24±0.47 mmol/l, 13.94±3.61 µU/ml, 1.73±0.40; p<0.001). Women with HOMA-IR ≥1.7 had a 7.94-fold increased risk of preeclampsia (95% CI: 2.87–21.98). Insulin resistance was strongly correlated with systolic (r=0.755) and diastolic (r=0.774) blood pressure (p<0.001). Conclusions: Elevated insulin resistance is significantly associated with preeclampsia and blood pressure elevation, indicating its potential utility as an early biomarker for the risk assessment and prevention of preeclampsia.